Evaluation of Effectiveness of an Online Selfdirected Learning Programme in Biochemistry for First Year Medical Undergraduate Students: A Quasi-experimental Study - Maitreyee Doijode Satyanarayan; Shivashankara Arnadi Ramachandrayya; Malathi Mala (Journal of Clinical and Diagnostic Research, 2024)
Introduction: Self-directed Learning (SDL) has been suggested as a principle of adult learning to promote lifelong learning abilities among students. Though SDL is not a new concept, there is a lack of uniform implementation across the institutions in India. The Competency-based Medical Education (CBME) proposed by the National Medical Commission in 2019 has emphasised SDL for medical students. Aim: To evaluate the effectiveness of an online, case-based SDL activity in Biochemistry for the first-year MBBS students. Materials and Methods: This was a quasi-experimental study conducted at Father Muller Medical College, Mangaluru, Karnataka, India from May to July 2021. A purposive sampling technique was used, and 138 first-year MBBS students were enrolled for the research. The topic of lipid metabolism was chosen for SDL. Parallel to the online didactic lectures, a case-based, team-based, online SDL was implemented. Students were provided with case scenarios and were instructed to discuss the case scenarios and find answers to the accompanying questions in allotted groups for 15 days. A three-hour session was held for the presentation of the SDL, followed by a post-test and reflections of students. The data were analysed using Statistical Package for Social Sciences (SPSS) version 25.0. The significance of the difference in pretest and post-test scores was assessed by paired t-test, and the level of significance was set at a p-value <0.05. Qualitative data were subjected to descriptive statistics, and thematic analysis of reflections was conducted. Results: The average post-test score of the participants was significantly higher by 99.3% compared to the pretest score (p-value <0.001). On average, 108 out of 138 (78.2%) agreed (agree/strongly agree) that SDL helped them to achieve the learning objectives,115 (83.3%) agreed that SDL helped them to develop as lifelong learners, 115 (83.3%) agreed that SDL helped them to develop as a health professional, and 83 (60.1%) agreed that enjoyed learning in online mode. The inclination of 110 (79.7%) students to have more SDL sessions in the future shows a behavioural change in favour of SDL. Time constraints and internet connectivity were the main challenges. Conclusion: SDL was effective and was received positively by the majority of the students. It is the need of the hour to develop lifelong learning and critical thinking among medical students and to make learning interesting with the use of case scenarios. Future research should assess the intermediate and long-term outcomes of case-based SDL on learning, behavioural changes, and its impact on patient care and the health of society.